Amino acid variations at a single residue in an autoimmune peptide profoundly affect its properties: T-cell activation, major histocompatibility complex binding, and ability to block experimental allergic encephalomyelitis. - Kumar, V (1990)
Myelin basic protein (MBP) or helper T cells reactive against MBP induce an autoimmune disease, experimental allergic encephalomyelitis, in B10.PL and PL/J inbred mice. In both strains, virtually the entire repertoire of MBP-specific T cells recognize an N-terminal peptide fragment in the context of the I-Au molecule encoded by the major histocompatibility complex (MHC) and utilize a very limited set of T-cell receptor genes. To delineate the nature of the trimolecular complex, consisting of the T-cell receptor, MBP-peptide fragment, and MHC molecule (I-Au), we have synthesized 13 variants of the 9-mer N-terminal immunodominant peptide differing at residue 4 and studied their immune recognition in vitro and in vivo. These substitutions have a striking range of effects on T-cell activation, ability to bind to the MHC molecule, and initiation of immune responses in vivo. An understanding of the autoimmune peptide/MHC/T-cell receptor interactions allowed us to design variant 9-mer peptides that have high affinity for an MHC molecule and are effective in blocking experimental allergic encephalomyelitis, possibly through two distinct mechanisms, peripheral T-cell tolerance and the inhibition of binding of the encephalitogenic peptide to the MHC molecules.